Chemical Reaction Engineering : A Computer-Aided Approach - Salmi, Tapio; Hernández Carucci, José Rafael; Wärnå, Johan; de Araújo Filho, César A. (De Gruyter Textbook, 2020)
This book illustrates how models of chemical reactors are built up in a systematic manner, step by step. The authors also outline how the numerical solution algorithms for reactor models are selected, as well as how computer codes are written for numerical performance, with a focus on MATLAB and Fortran. Examples solved in MATLAB and simulations performed in Fortran are included for demonstration purposes.